Diets Containing Shiitake Mushroom Reduce Serum Lipids and Serum Lipophilic Antioxidant Capacity in Rats. Issue 12 (19th October 2016) - Yu, Shanggong; Wu, Xianli; Ferguson, Matthew; Simmen, Rosalia CM; Cleves, Mario A; Simmen, Frank A; Fang, Nianbai
Abstract: Background: We previously reported that dietary intake of shiitake mushroom (SM; Lentinus edodes ) decreased serum concentrations of polar lipids in male rats. Objective: This study evaluated the dietary effects of SM on serum cholesterol–related and serum antioxidant indexes in rats of both sexes. Methods: Sprague-Dawley rats [38 dams and their offspring (20 males and 20 females/diet)] were fed diets containing 0 (control), 1%, 4%, or 10% (wt:wt) SM powder from gestation day 4 through to postnatal day (PND) 126. Biochemical indexes were monitored during the midgrowth phase (PNDs 50–66). Results: The food consumption by offspring fed the control diet and diets supplemented with SM was not different when measured on PND 65. However, the 4% and 10% SM diets resulted in male rats with 7% lower body weights than those of the other 2 groups on PND 66. SM consumption dose-dependently decreased the concentrations of lipidemia-related factors in sera, irrespective of sex. At PND 50, serum concentrations of total cholesterol, HDL cholesterol, and non-HDL cholesterol in SM-fed male and female rats were generally lower (3–27%) than those in the corresponding control groups. Consumption of the 10% SM diet resulted in significantly decreased (55%) serum triglyceride concentrations relative to the control groups for both sexes. The 10% SM diet elicited a 62% reduction of serum leptin concentrations in females but not in males, and this same diet increased serum insulin (137%) and decreased serum glucose (15%) in males compared with controls. Serum lipophilic antioxidant capacity in males and females fed SM diets was generally lower (31–86%) than that in the control groups. Conclusion: SM decreased the concentrations of lipidemia-related factors in rat sera irrespective of sex. The SM-elicited reduction of lipophilic antioxidant capacity irrespective of sex may reflect a lower pro-oxidative state and, hence, improved metabolic profile.